Dynamics of the Islamic Education Curriculum in Madrasah: Study K-13 and Merdeka Curriculum - Saiful Anwar; Ishomuddin Ishomuddin; Faridi Faridi (Yayasan Letiges Konsultan Sosial, 2023)
Since the new order era, the Indonesian education curriculum has undergone eight revisions, from the 1968 curriculum to the most recent, the Merdeka Curriculum. Each curriculum has its unique characteristics, including the 2013 Curriculum and the Merdeka Curriculum which are currently being implemented. Madrasas are the subject and aim of the research, namely explaining the dynamics of madrasa curriculum development in 2013-2023. Using a qualitative approach with a type of literature review, data sources from relevant books and journal articles, and data analysis using condensation, presentation and conclusion. The results of the research show that in the 2013 curriculum and the Merdeka Curriculum there are certainly developments in terms of curriculum based on the continued development of science and technology. The 2013 curriculum is designed to improve character education, increase locally-focused education, and create a fun and friendly educational environment. The independent learning program is a flexible program focusing on essential material, character development and student abilities. The Islamic education subjects found in madrasas consist of four groups: Al-Qur’an Hadith, Fiqh, Aqidah Akhlak, and SKI, all of which are regulated by Minister of Religion regulations under the auspices of the Ministry of Religion.